The Use of Busuu Application to Improve Learning Vocabulary in SMP Negeri 35 Samarinda - Della Fitri Arza; Abdul Rohman; Widi Syahtia Pane (Wadah Inovasi Indonesia, 2023)
Background: Learning activities are introduced through interactive activities, including pronunciation vocabulary, grammar, dialogue, reading, translation, peer correction, voice recording, and chat (Brick, 2011; Boyd & Ellison, 2007). Methodology: The research was conducted as CAR (Classroom Action Research) because this design is the right design to improve students’ vocabulary using Busuu Application. Findings: The researcher would explain to them as follow: Cycle one consisted of three meetings. Each meeting was conducted for 30 minutes, the researcher designed the lesson plan and instrument. The topics which were used in cycle one were multiple choice questions. Conclusion: With Busuu Application the students could enjoy learning English and they more are interested. Moreover, it was proved from the mean score of the post-test was 50.45 become 78.19 as a result, Busuu Application was effective in improving the vocabulary of students. Originality: Busuu Application was effective in improving the vocabulary of students. It was shown by the results of post- test and pre-test cycle one and cycle two of SMP Negeri 35 Samarinda of Eighth Grade Students. Moreover, it was proved from the mean score of the post-test was 50.45 become 78.19 as a result, Busuu Application was effective in improving the vocabulary of students. With Busuu Application the students could enjoy learning English and they more are interested. This could also improve students motivation